Knowledge Acquisition in Times of the 2020 Coronavirus Pandemic: Evidence from a Four-Wave Panel Study. (30th August 2021) - Damstra, Alyt; Hameleers, Michael
Abstract: This paper focuses on the accuracy of COVID-19-related knowledge during the 2020 pandemic. We look at the effects of traditional vs. digital news use and distinguish between positive (number of recoveries) and negative (number of casualties) knowledge. Importantly, the moderating role of crisis context is examined when tracing media effects on knowledge. Relying on a four-wave panel survey fielded in the Netherlands, we find that people's knowledge became more accurate over the course of the crisis. News exposure did not lead to more accuracy, in fact, a negative relation was found. The impact of digital news use weakened as the crisis continued.